Interactions of π -mesons of kinetic energy 915 Mev with carbon nuclei - Abrattista, N.; Blasco, M.; Mongelli, S.; Romano, A.; Waloschek, Pedro; Perez-Ferreira, Emma (Societa italiana di fisica, 1962)
Fil: Abrattista, N. Istituto di Fisica dell'Université Bari; Italia